A Design For Local Production Of Aluminium Alloy (Al 6063) Based On The Optimization Of The Elastoplastic Response Of Castings - Malomo, B.O.; Popoola, O.T. (Ife Journal of Technology, 2010)
A high quality product at a relatively minimal cost is the goal of modern manufacturing. To achieve this, the foremost strategy is to consider at the product design stage, the optimal levels of production process parameters. This paper provides an insight into the robust manufacture of die-cast aluminium alloy Al 6063 based on the production process parameters of pouring temperature (T), die-preheat temperature (Tm) and the amplitude of vibration during casting (V). An experimental design based on the Taguchi’s orthogonal array of L8 (25) was formulated and carried out at two levels of T (6600C, 7200C), Tm (1300C, 2500C) and V (200µm, 600µm). The data obtained from mechanical tests of each cast was analysed by the signal to noise (S/N) ratio and ANOVA statistics to determine the optimal combination of process parameters most consistent with product performance. Numerical validation of the experimental approach was subsequently carried out using the Finite Element (FEM) code of COMSOL Multiphysics. Test results show that the most significant values for optimisation is set at the process parameters combination of (6600C, 2500C and 200µm) for T, Tm and V from which the predicted values of the hardness, percentage elongation to fracture, yield strength, and ultimate tensile strength were given as 43.75, 1.39%, 29.80MN/m2, 88.34MN/m2 respectively. The details of numerical investigations in terms of the elastic properties of cast products were also found to be in close agreement with the statistical estimates.